2021
DOI: 10.3390/app11167728
|View full text |Cite
|
Sign up to set email alerts
|

Low-Cost and Easily Fabricated Ultrasound-Guided Breast Phantom for Breast Biopsy Training

Abstract: We aimed to develop an inexpensive and easy-to-fabricate gelatin-based training phantom for improving the breast biopsy skill and confidence level of residents. Young’s modulus and acoustic properties of the gelatin tissue phantom and simulated tumors were investigated. Six residents were requested to evaluate the effectiveness of the breast phantom. The results showed that 83% (n = 5) of the participants agreed that the ultrasound image quality produced by the breast phantom was excellent or good. Only 17% (n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Ashurst et al 50 noted that the use of mechanical simulators enhanced the performance of trainees in applying cricoid pressure. Furthermore, Ng et al 51 studied breast biopsy skill using a biomechanically compliant simulator. The results showed that the confidence levels of the participants greatly increased through simulation training 51 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ashurst et al 50 noted that the use of mechanical simulators enhanced the performance of trainees in applying cricoid pressure. Furthermore, Ng et al 51 studied breast biopsy skill using a biomechanically compliant simulator. The results showed that the confidence levels of the participants greatly increased through simulation training 51 .…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Ng et al 51 studied breast biopsy skill using a biomechanically compliant simulator. The results showed that the confidence levels of the participants greatly increased through simulation training 51 . The studies mentioned demonstrate the effectiveness of relevant mechanical simulators in medical education.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the combination of Thermoplastic Polyurethane (TPU) and Acrylonitrile Butadiene Styrene (ABS) can be used to make a phantom allowing needle insertion training [8]. Models based on gelatin can also be used [9]. However, these solutions require manufacturing new products to reproduce different behaviors.…”
Section: Haptic Devices Used For Needle Insertion Simulatorsmentioning
confidence: 99%
“…In fact, many institutions preferred home‐made alternatives for their studies, utilising food or animal products, since they are low cost and easy to make. Turkey or chicken breast, as well as gel‐based tissue‐mimicking phantoms are commonly used to simulate soft tissue 33 . The inserts could be of liquid or solid content depending on the type of biopsy procedure that will be followed.…”
Section: Introductionmentioning
confidence: 99%
“…The inserts could be of liquid or solid content depending on the type of biopsy procedure that will be followed. For freehand US‐guided breast biopsy training, raw materials including olives with pimentos, grapes, capers, strawberries, peas and potatoes have been proposed in the literature as tumour mimics 33 …”
Section: Introductionmentioning
confidence: 99%